Sports television on Russian state TV channels in the winter seasons 2021-2024 - Shvetsov A.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the composition and dynamics of indicators of sports programs on publicly available Russian state television channels in the winter competition seasons of 2021-2024. Methods and structure of the study. An analysis, comparison and generalization of the indicators of sports programs on Russian state television was conducted. Results and conclusions. The IOC’s decision to suspend Russian athletes from participating in international competitions from March 2022 led to the forced change of international tournaments with Russian on the broadcast network of state TV channels. Two years of isolation of Russian athletes from major international competitions did not change the structure of sports programs in the winter seasons of 2021-2024, but played a major role in the sharp decline in interest in these programs on Russian television. So, after the successful Olympic season 21/22, the ratings of sports programs in the next two winter seasons decreased at least 2-3,5 times.